The value of vulnerability: The transformative capacity of risky trust - Luigino Bruni; Fabio Tufano (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2016)
The 'grammar of trust' is one of the most explored loci in behavioural and experimental economics. This experimental study aims at contributing to the understanding of new dimensions of trust by exploring how risky trust may foster a trustee's behavioural change. It investigates trustee's behaviour when the intentional trustor's risk is both manifestly salient and dependent upon the trustee's revealed type, namely trustworthy or untrustworthy. The results support the transformative nature of risky trust, which generates more trustworthy and reciprocal behaviour in untrustworthy people.
Keywords: C72; C92; D01; 330; experiment; gift-exchange game; organization; trust; vulnerability